2002
DOI: 10.1111/j.1530-0277.2002.tb02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Heart Rate Responses to Public Speaking in Individuals With Alcohol Dependence

Abstract: Comparable cardiovascular responses to orthostasis in controls and AD subjects suggest intact reflex control of circulation. AD subjects had blunted HR responses to public speaking; this is consistent with the attenuated cortisol responses observed in this sample and in previous studies. This suggests a possible alteration in limbic system regulation of hypothalamic and brainstem responses to psychological stress. Cardiovascular responses of AD subjects that are inconsistent with subjective accounts of tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 23 publications
5
24
1
Order By: Relevance
“…However, our findings are very much in line with those from previous research showing that smokers are characterised by relatively blunted cardiovascular (Girdler et al, 1997;Phillips et al, 2009;Roy et al, 1994;Sheffield et al, 1997;Straneva et al, 2000) and cortisol (al'Absi et al, 2003;Kirschbaum et al, 1993Kirschbaum et al, , 1994Rohleder and Kirschbaum, 2006) reactivity. They also resonate with the findings from studies linking alcoholism (Lovallo et al, 2000;Panknin et al, 2002) and risk of alcohol dependence (Sorocco et al, 2006) with blunted cardiovascular and cortisol reactivity. The present results also offer further challenge to the assumption that low stress reactivity is necessarily benign (Carroll et al, 2009, in press).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, our findings are very much in line with those from previous research showing that smokers are characterised by relatively blunted cardiovascular (Girdler et al, 1997;Phillips et al, 2009;Roy et al, 1994;Sheffield et al, 1997;Straneva et al, 2000) and cortisol (al'Absi et al, 2003;Kirschbaum et al, 1993Kirschbaum et al, , 1994Rohleder and Kirschbaum, 2006) reactivity. They also resonate with the findings from studies linking alcoholism (Lovallo et al, 2000;Panknin et al, 2002) and risk of alcohol dependence (Sorocco et al, 2006) with blunted cardiovascular and cortisol reactivity. The present results also offer further challenge to the assumption that low stress reactivity is necessarily benign (Carroll et al, 2009, in press).…”
Section: Discussionsupporting
confidence: 75%
“…Those addicted to alcohol have also been found to exhibit blunted cardiovascular and cortisol stress reactivity (Lovallo et al, 2000;Panknin et al, 2002). In addition, relatively low reactivity would appear to be a characteristic of non alcoholics with a family history of alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…The normal diurnal pattern suggested intact HPA function, while the patients' stress cortisol hyporesponsiveness may have reflected a difference in stressrelated neural inputs to the hypothalamus that are needed for a psychological stress reaction. In parallel with these HPA findings, we observed that the same patients had an attenuated heart rate response to public speaking stress, although their reflex heart rate and blood pressure changes to orthostatic stress were normal (Panknin et al, 2002). These HPA and cardiovascular findings are in agreement that the abstinent alcohol and polysubstance abusing patients had normal homeostatic regulation of visceral function, but that the neurological response to psychological stress was blunted.…”
Section: Introductionsupporting
confidence: 80%
“…28 In contrast, one other study found that alcohol-dependent patients show a blunted blood pressure response to public speaking stress, although this alteration was thought be caused by a blunted perception of the social threat at the level of the central nervous system. 29 In the present study, no differential change in blood pressure was found in the 2 groups, with alcoholic subjects and controls showing similar increases of blood pressure in response to sleep loss. However, to allow for comparison of the effects of alcohol dependence on cardiovascular responses without the confounding effects of hypertensive medications, this study excluded alcoholic subjects who were currently being treated for hypertension.…”
Section: Irwin and Ziegler Sleep Deprivation And Sympathetic Activaticontrasting
confidence: 57%